Validity and Reliability Test of the Menstrual Cycle Questionnaire for Adolescent Girls - Alifia Candra Puriastuti; Surya Adi Saputra; Zumroh Hasanah; Dessy Amelia (Poltekkes Kemenkes Tanjung Karang, 2026)
Reproductive health is defined as complete physical, mental, and social well-being in all aspects of the reproductive system, functions, and processes, not just a condition free from disease or disability. So far, there has been no standard instrument to collect data on adolescent menstrual cycle conditions. This study aims to test the validity and reliability of the questionnaire used to collect data on the menstrual cycle of female adolescents. The design of this study is cross-sectional; the questionnaire was developed through a comprehensive literature review. The questionnaire was tested for construct validity through a statistical analysis. The population in this study was adolescent girls, aged 12-15 years, who had experienced menarche. The number of respondents in this study is 40. The results of the construction validity test in this study showed that the r table value (0.358-0.540) was greater than the r count (0.3044), indicating validity. Meanwhile, the reliability test in this study was determined using Cronbach's Alpha, which was 0.706. The validity and reliability tests of the menstrual cycle questionnaire for adolescent girls yielded strong results, indicating that the questionnaire can be used as a reliable data-collection tool.